Intestinal dysbiosis and obesity in modern society: A review of evidence and perspectives on therapeutic interventions (Research, Society and Development, 2024)
Introduction: Dysregulation of the intestinal microbiota refers to alterations in the normal and healthy balance of bacteria inhabiting the gastrointestinal tract. This dysbiosis may play a significant role in the development and progression of various diseases, as the intestinal microbiome performs crucial functions in maintaining host health. Objective: This study aimed to review and discuss the evidence regarding the relationship between intestinal dysbiosis and obesity. Additionally, we aimed to describe the potential interventions available for the prevention and treatment of individuals affected by these dysregulations. Methods: A narrative review was conducted to select articles to seek current scientific evidence on the topic. The following databases were utilized for this review: Google Scholar, LILACS, National Library of Medicine (PubMed), and SciELO. The final number of articles was determined through a similarity analysis with the theme, taking into consideration the research objective. Results: After the searches, 42 articles were selected for analysis and discussion. The review revealed that modern dietary patterns are the primary cause of modulating the intestinal microbiota, and the products of dysregulated metabolism contribute to alterations in hormonal axes. Conclusion: It was concluded that obesity treatment should be considered within a multidisciplinary framework, including cautionary measures for all environmental factors that can modulate it.